Clinical Risk Factors for Postoperative Atrial Fibrillation among Patients after Cardiac Surgery - Yamashita, Kennosuke; Hu, Nan; Ranjan, Ravi; Selzman, Craig H.; Dosdall, Derek J. (The Thoracic and Cardiovascular Surgeon, 2019)
Background Postoperative atrial fibrillation (POAF) is a common arrhythmia following cardiac surgery and is associated with increased health-care costs, complications, and mortality. The etiology of POAF is incompletely understood and its prediction remains suboptimal. Using data from published studies, we performed a systemic review and meta-analysis to identify preoperative clinical risk factors associated with patients at increased risk of POAF.Methods A systematic search of PubMed, MEDLINE, and EMBASE databases was performed.Results Twenty-four studies that reported univariate analysis results regarding POAF risk factors, published from 2001 to May 2017, were included in this meta-analysis with a total number of 36,834 subjects. Eighteen studies were performed in the United States and Europe and 16 studies were prospective cohort studies. The standardized mean difference (SMD) between POAF and non-POAF groups was significantly different (reported as [SMD: 95% confidence interval, CI]) for age (0.55: 0.47–0.63), left atrial diameter (0.45: 0.15–0.75), and left ventricular ejection fraction (0.30: 0.14–0.47). The pooled odds ratios (ORs) (reported as [OR: 95% CI]) demonstrated that heart failure (1.56: 1.31–1.96), chronic obstructive pulmonary disease (1.36: 1.13–1.64), hypertension (1.29: 1.12–1.48), and myocardial infarction (1.18: 1.05–1.34) were significant predictors of POAF incidence, while diabetes was marginally significant (1.06: 1.00–1.13).Conclusion The present analysis suggested that older age and history of heart failure were significant risk factors for POAF consistently whether the included studies were prospective or retrospective datasets.
Keywords: atrial fibrillation; cardiac surgery; odds ratios; standardized mean difference